Cutaneous neoplasm in Phaeotabanus litigiosus (Diptera, Tabanidae) collected on the Marambaia Island, Rio de Janeiro, Brazil - RR Guimarães; RR Guimarães-Junior; RS Harlan-Ronald; R Rodrigues-Guimarães; FL Carvalho; MLC Araújo-Junior; RW Carvalho (Invertebrate Survival Journal, 2016)
A female specimen of Phaeotabanus litigiosus (Diptera: Tabanidae) collected on Marambaia Island was found with a tumor in the abdominal integument. Histopathological examination revealed an epithelial dysplasia with anisokariosis and hyperchromasia. This is the first record of a neoplasm found in tabanid collected from natural environment. Key Words: Atlantic island; displasia; horse fly; insect disease; insect vector; neotropical region